An Overview of Anthropological and Sociological Research at the Faculty of Social Sciences, Universiti Malaysia Sarawak - Poline, Bala (Springer Singapore, 2017)
In order to make sense of contemporary and ongoing anthropological and sociological research activities at the Faculty of Social Sciences, Universiti Malaysia Sarawak (UNIMAS) it is important to highlight different levels of factors that have shaped and influenced the sort of research agendas and activities carried out by members of the faculty (and also the Institute of East Asian Studies and now known as Institute of Borneo Studies) over the past 20 years. The discussion also reveals the social and political milieu within which research has been carried out and, at the same time, throws light on ways in which the first university in Sarawak has addressed the concerns of society.